Estimation Of The Sustanaible Potential Of Red Snapper (Lutjanus Malabaricus) Landed At The Sibolga Archipelago Fishing Port - Fuah, Ricky Winrison; Rahayu, Rosi; Umam, Hairul; Pandang, Ivonda Vicanda; Agustina, Imelda (Jurnal Perikanan dan Kelautan, 2025)
Continuous and uncontrolled fishing of red snapper will cause fish stocks to degrade, while there is no recruitment process and if caught without good management. Therefore, it is necessary to study the estimation of the sustainable potential of red snapper. The purpose of this study was to calculate Catch Per Unit Effort (CPUE) and assess the value of Maximum Sustainable Yield (MSY) and Total Allowable Catch (TAC/JTB) of red snapper. The research was conducted at Sibolga VAT with survey data collection method, while the surplus production method with Schaefer model. The results showed that the standardized CPUE value in 2018 was 0.060 tons/trip, in 2019 it decreased to 0.037 tons/trip, in 2020 it decreased to 0.029 tons/trip, in 2021 it increased to 0.041 tons/trip, and in 2022 it increased to 0.060 tons/trip, then a decrease occurred again in 2023 which was 0.055 tons/trip. The overall CMSY value calculated using the Scheafer model was 122.2 tons, so it can be concluded that the fishing status is fully exploited and overfished. While the FMSY value is obtained at 3201 trips, where the status is overfished and fully exploited because the fishing effort each year is above the FMSY value. The total allowable catch (TAC/JTB) is 97.8 tons.